Monodisperse Dual-Functional Upconversion Nanoparticles Enabled Near-Infrared Organolead Halide Perovskite Solar Cells - He, Ming; Pang, Xinchang; Liu, Xueqin; Jiang, Beibei; He, Yanjie; Snaith, Henry; Lin, Zhiqun (Angewandte Chemie International Edition, 2016)
Extending the spectral absorption of organolead halide perovskite solar cells from visible into near‐infrared (NIR) range renders the minimization of non‐absorption loss of solar photons with improved energy alignment. Herein, we report on, for the first time, a viable strategy of capitalizing on judiciously synthesized monodisperse NaYF4:Yb/Er upconversion nanoparticles (UCNPs) as the mesoporous electrode for CH3NH3PbI3 perovskite solar cells and more importantly confer perovskite solar cells to be operative under NIR light. Uniform NaYF4:Yb/Er UCNPs are first crafted by employing rationally designed double hydrophilic star‐like poly(acrylic acid)‐block‐poly(ethylene oxide) (PAA‐b‐PEO) diblock copolymer as nanoreactor, imparting the solubility of UCNPs and the tunability of film porosity during the manufacturing process. The subsequent incorporation of NaYF4:Yb/Er UCNPs as the mesoporous electrode led to a high efficiency of 17.8 %, which was further increased to 18.1 % upon NIR irradiation. The in situ integration of upconversion materials as functional components of perovskite solar cells offers the expanded flexibility for engineering the device architecture and broadening the solar spectral use. A strategy for integrating NaYF4:Yb/Er upconversion nanoparticles as a mesoporous electrode into CH3NH3PbI3 perovskite solar cells makes it possible to operate the cells with near‐infrared light. The in situ integration of upconversion materials as functional components in perovskite solar cells offers flexibility for engineering the device architecture and broadening the use of solar radiation.